Analysis of barrier height inhomogeneity in Au/n-GaAs Schottky barrier diodes by Tung model - Soylu, Murat; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2010)
The apparent barrier heights and ideality factors of identically fabricated gold Schottky contacts on n-GaAs (14 dots) were determined from by forward bias current-voltage characteristics at room temperature. A statistical study on the experimental barrier heights and ideality factors of the diodes was performed. The obtained results indicate that the barrier heights and ideality factor parameters of Schottky diodes are different from one diode to another, even if they are identically prepared. The experimental BH and ideality factor distributions obtained from current-voltage characteristics were fitted by a Gaussian function, and their mean values were found to be 0.664 +/- 0.024 and 1.700 +/- 0.129 eV, respectively. The lateral homogeneous BH value of 0.738 eV for the gold Schottky contacts on n-GaAs was obtained from Phi(b0) VS n plot by using n(if) = 1.026 and Delta Phi(inf) = 42 meV. It is concluded that the higher ideality factors accompany with the lower BHs or vice versa due to inhomogeneities. Also, a theoretical modelling of the formation mechanism of the Schottky barrier across the metal-semiconductor interfaces was successfully applied with the assumption of a statistical distribution of the patch characteristics. This model was assisted to lead to the explanation of many anomalies in the experimental results. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: GaAs; Schottky diode; I-V measurements; Gaussian distribution; Barrier inhomogeneities